CONSTRUCTION AND PRACTICE OF A DUAL-TRACK EDUCATION MODEL IN INTANGIBLE CULTURAL HERITAGE TRANSMISSION-A CASE STUDY OF YI ETHNIC CLOTHING SKILLS IN LIANGSHAN - Zheng, Yuwei; Zainuddin, Nasaie (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
Under the impact of globalization and modernization, Intangible Cultural Heritage (ICH), such as the clothing of the Yi nationality in Liangshan, faces the severe dilemma of inheritance discontinuity and skill loss. Education, as the core means of the living inheritance of ICH, has problems such as the singularity of the model and the disconnection between supply and demand that need to be urgently addressed. Based on critical ethnography and Community-Based Participatory Action Research (CPAR) methods, this study focuses on the educational practices in the inheritance of Yi ethnic clothing skills. It constructs a dual-track education model of “traditional track + modern track” through in-depth interviews with 50 key informants and a survey of 450 structured questionnaires. Concurrently, the study discovered that the traditional track, centered on the clan-apprenticeship system, activates the intergenerational oral teaching and mental instruction mechanism through the “1+5” inheritance unit, effectively preserving core skills and cultural genes. Furthermore, the modern track, based on situational learning theory, establishes an educational pathway of “dual-mentorship + digital media + cross-sector collaboration,” enhancing the modern adaptability of skills and youth participation.According to the ADAPT (Authenticity, Development, Adaptation, Participation, Transmission) matrix assessment, this model increased the retention rate of young practitioners from 28% to 46% and improved cultural identity scores by 35%, achieving a dynamic balance between cultural authenticity and educational effectiveness. Overall, this study enriches the theoretical framework of ICH education and provides a replicable educational model for the transmission of minority cultural heritage. It also holds significant practical value for integrating ICH into both formal and informal education systems.